Recruiting Participants with Complex Communication Access Needs in Social Science Research: Issues of Capacity and Consent - Dee-Price, Betty-Jean (Issues in Social Science, 2024)
Qualitative research assumes verbal and written communication ability from participants. Legitimised by the ethical pillars of ‘capacity’ and ‘consent’, articulate speech acts are the hidden ticket to research inclusion. The knowledge contribution of people with complex communication access needs is left off; a situation that undermines social science, reinforces disability exclusion paradigms and bypasses opportunities to remediate the problem. In this study, an important part of capacity assessment was transferred from the researcher to the prospective participants to sign off on the investigators’ capacity to communicate using alternative augmentative communication. The article begins with an exploration of the problem before describing the adaptations made and implemented in this study and their implications for social science.